2020
DOI: 10.1002/jssc.201900882
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic separation simulation of metal‐chelating peptides from surface plasmon resonance binding parameters

Abstract: Funding information LUE IMPACT BiomoleculesSome metal-chelating peptides have antioxidant properties, with potential nutrition, health, and cosmetics applications. This study aimed to simulate their separation on immobilized metal ion affinity chromatography from their affinity constant for immobilized metal ion determined in surface plasmon resonance, both technics are based on peptide-metal ion interactions. In our approach, first, the affinity constant of synthetic peptides was determined by surface plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 23 publications
(29 reference statements)
0
10
0
Order By: Relevance
“…Finally, the output data is the profile of peptide concentration as a function of time, from which the simulated retention time of a peptide is obtained, as reported in the proof of concept established by Muhr and colleagues. 210 On the other hand, experiments are done in IMAC, and experimental retention time is compared with the simulated retention time in order to validate the chromatography modelling. More recently, in our team, Irankunda et al (2024) deciphered the peptide-metal interaction involved in IMAC and SPR technology of 22 peptides.…”
Section: Simulation Of Imac Separation From Spr Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the output data is the profile of peptide concentration as a function of time, from which the simulated retention time of a peptide is obtained, as reported in the proof of concept established by Muhr and colleagues. 210 On the other hand, experiments are done in IMAC, and experimental retention time is compared with the simulated retention time in order to validate the chromatography modelling. More recently, in our team, Irankunda et al (2024) deciphered the peptide-metal interaction involved in IMAC and SPR technology of 22 peptides.…”
Section: Simulation Of Imac Separation From Spr Datamentioning
confidence: 99%
“…209 The finding indicated that most of the studied peptides with a high retention time in IMAC also exhibited a high affinity in SPR, which agreed with Muhr and colleagues. 210 6. Chemical interaction between peptide and metal ions 6.1 Fourier-transform infrared spectroscopy Fourier-transform infrared spectroscopy (FTIR) gives information about the chemical composition and conformational structure of food components.…”
Section: Simulation Of Imac Separation From Spr Datamentioning
confidence: 99%
“…Catalytic metal can accelerate the decomposition of oil oxidation primary products to generate free radicals as shown in Scheme 4 (Muhr et al, 2020). The catalysis of catalytic metal depends on their ability to react with unoxidized oil to form hydroperoxides (Juita et al, 2011).…”
Section: Inhibiting the Activity Of Catalytic Metal Ionsmentioning
confidence: 99%
“…In addition, surface plasmon resonance (SPR) was reported to compare the affinity constant of different tagged proteins bound to metal ions or to study the affinity of His-tag peptides to Ni 2+ ions . Recently, our team developed a strategy to screen MCPs using affinity constants determined in SPR and to simulate their IMAC separation . Like SPR, the newly introduced switchSENSE technology allows to analyze biomolecular interactions in real time.…”
Section: Introductionmentioning
confidence: 99%
“…23 Recently, our team developed a strategy to screen MCPs using affinity constants determined in SPR 24 and to simulate their IMAC separation. 25 Like SPR, the newly introduced switchSENSE technology allows to analyze biomolecular interactions in real time. The originality of this latter technology is based on the use of electro-switchable fluorescent DNA nanolevers in which one DNA strand bears a fluorophore while its complementary strand is functionalized by a capture molecule (i.e., complexing agent), itself coupled to a ligand (e.g., metal ion).…”
Section: ■ Introductionmentioning
confidence: 99%